Strategic moves - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2011)
Stone Barrington's undercover dealings with MI6 have brought in a big new client for the Woodman & Weld law firm, and the firm is willing to pay Stone a huge bonus and make him a partner. But a murder close to home and a request from the CIA to help transport a fugitive, Erwin Gelbhardt, from Spain to the U.S., bring him back to earth.